The Impact of Training and Development on Intrapreneurial Behavior - Matloob, Haroon Ahmed; Raju, Valliappan (Journal of Innovation and Management, 2020)
The purpose of this study is to screen the data of the study and conduct a preliminary analysis on the relationship between training and development and intrapreneurial behavior. A sum of 600 questionnaires were distributed to the employees in oil and gas industry in Iraq. The proportionate stratified sampling method was used; equally all necessary processes were followed to satisfy the multivariate analysis assumptions. The internal consistency, convergent validity and discriminant validity were all tested. The data were arranged in the smart pls software version 3.2.8. The result shows the data of training and development have a significant impact on intrapreneurial behaviour.